From International Maritime Satellite Organization (INMARSAT) to International Mobile Satellite Organization (IMSO) - A. V. Luk(i)yanova (Московский журнал международного права)
In the article a retrospective analysis of developing space cooperation is carried out within the framework of International Maritime Satellite Organization’ (INMARSAT) activity as an original form of International Mobile Satellite Organization (IMSO) to solve problems of World Ocean and space.The article investigates into the history of creation and legal foundation for international cooperation of the above-mentioned organization.The contemporary legal aspects of IMSO are analyzed. In addition, the trends of development of organization activities are revealed for the purpose of protecting the Russian Federation’s interests to provide security of navigation in sea areas, security of Russian-flag vessels, crews and persons aboard the vessels.